Implementation of Telenursing on The Behavior of Type 2 Diabetic Foot Care - Mutiudin, Ade Iwan; Jundiah, Siti; Intan Husnul Khatimah, Nur; Maryani, Yani; Aulia Putri, Natasya; Amara Davaina, Siti (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Diabetes is one of the health emergencies that require serious treatment. Diabetic foot complications have an impact on the quality of life and have the potential to threaten the lives of sufferers. Telenursing intervention programs have a lot of influence in improving health. However, there has been no research that proves that this method can have a positive impact on foot care behavior. The purpose of this study was to analyze the implementation of telenursing on foot care behavior. The research design used pre-experimental, with a one group pre-test - post-test design. 23 samples were obtained through purposive sampling techniques. The instrument used was Foot Self-Care (DFSQ-UMA). Data normality test using Shapiro - Wilk, and paired sample t-test. The results of the statistical test showed a p-value of 0.001 (p <0.05), which means that telenursing interventions are effective in improving foot care behavior. Telenursing programs need to be implemented in communities and various health facilities by involving families as an innovative solution for foot care education for diabetes mellitus patients.